Postoperative analgesic effect of acupuncture in laparoscopic cholecystectomy surgery - (:unkn) unknown (KARE PUBL, 2015)
Objectives: In surgery clinics, postoperative pain is a common occurrence and care is needed in its treatment. One form of treatment is various acupuncture techniques. This study investigated the effect of acupuncture on postoperative analgesia in patients undergoing laparoscopic cholecystectomy. Methods: A total of 59 patients undergoing laparoscopic cholecystectomy were included in the study; 31 comprised the acupuncture group (Group A), and 29 constituted the control group (group C). All patients underwent standard anesthesia procedures. Patient-controlled analgesia with tramadol was administered postoperatively. Patients' postoperative pain scores, results of the satisfaction questionnaire and amounts of tramadol used were recorded. Postoperative 0, 1st, 2nd, 6th, 12th and 18th hour controls were performed. Results: A comparison of the groups showed Group A pain scores to be significantly lower statistically than those of Group C at all postoperative controls. There was no statistically significant difference for postoperative analgesic consumption and satisfaction level between the groups. Conclusion: Despite detection of a reduction in postoperative pain scores, the application of acupuncture did not cause any change in the consumption of tramadol.
Keywords: Acupuncture; postoperative pain; patient control analgesia; tramadol; ELECTRICAL NERVE-STIMULATION; PAIN; REQUIREMENT; ELECTROACUPUNCTURE; ACUPOINT; NAUSEA